2015
DOI: 10.1063/1.4921596
|View full text |Cite
|
Sign up to set email alerts
|

Properties of three-dimensional structures prepared by Ge dewetting from Si(111) at high temperatures

Abstract: The formation of three-dimensional (3D) structures during Ge deposition on Si(111) at about 800 °C is studied with scanning tunneling, Kelvin probe and electron microscopies, and scanning tunneling and Raman spectroscopies. The observed surface morphology is formed by dewetting of Ge from Si(111), since it occurs mainly by means of minimization of surface and interfacial energies. The dewetting proceeds through massive Si eroding around growing 3D structures, providing them to be composed of SiGe with about a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…It is widely used for the formation of various metal layer surface morphologies. [1][2][3] The dewetting of SiGe layers was observed recently on both Si(111) 4 and Si(100) 5,6 substrates. A detailed investigation of the dewetting process would be thus highly desirable both from the scientific and applied viewpoints.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…It is widely used for the formation of various metal layer surface morphologies. [1][2][3] The dewetting of SiGe layers was observed recently on both Si(111) 4 and Si(100) 5,6 substrates. A detailed investigation of the dewetting process would be thus highly desirable both from the scientific and applied viewpoints.…”
Section: Introductionmentioning
confidence: 87%
“…This shift may be caused by the lattice strain. Using the relation e S ¼ Àðx SS À 520:6Þ 830 (4) derived from Eq. (1a) with x ¼ 0, we obtain a compressive stress in the Si substrate below the continuous film.…”
Section: Raman Spectroscopy Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…As suggested here, the porous SiGe layer formation is the result of surface melting which is significantly facilitated by the strong stain caused by the Si-Ge lattice mismatch. It can also be suggested that the same reason is responsible for the porous SiGe layer formation on Si(111) [ 16 , 22 ]. Under annealing at temperatures in the range from 700 to 900 °C, two processes compete with each other.…”
Section: Resultsmentioning
confidence: 99%